Técnicas de cultivo hidropónico en el rendimiento de Lactuca sativa L. Loreto - Ferro Heysen, Oscar Andre (2022)
Lettuce is one of the most important olericultural species in the tropics and is usually sown traditionally, but the use of hydroponics allows a substantial improvement in its growth and development. The main objective was to compare the effect of two hydroponic techniques on the yield of Lactuca sativa L. The seedbed was made in hydroponic seedling trays on whose smooth surface was placed wet table paper, the seeds are deposited in lines and uniformly, it is protected with a film of filter paper, the seedlings on average height of 5 cm were placed in sponge cones in a sheet of Flex pore floating in a box of 5. 0 cm high for growth and adaptation to culture in low conductivity nutrient solution, then after 15 days were planted in the boxes of the floating root technique (TRF) and in the tubes of the nutrient laminar flow technique (NFT), the boxes of 1.0 m x 1.0 m and 10.0 cm high at 1.0 m from soil level. The channels or tubes at 1.0 m from ground level at 0.20 m between tubes. It is concluded that there is a significant effect (p<0.01) for height, plant width, stem diameter and root weight and no significant effect (p>0.05) for root length and number of leaves. The TRF is statistically significant at NFT, for height (27.77 and 16.83 cm), plant width (26.73 and 20.33 cm), stem diameter (11.10 and 7.83 cm) and for root weight (11.13 and 8.0 g); while for root length the values differ numerically in RF with 8.10 cm and in NFT with 7.40 cm and quantity of leaves per plant in TRF with 11.27 and in NFT with 7.83. For yield there is significant effect (p<0.01) of the hydroponic technique for plant weight, the RF hydroponic technique has significant effect on average plant weight 96.73 g versus NFT technique with 46.6 g.